Structural components and factors of regional human capital development - V. V. Matveev; S. A. Ilminskaya (Вестник Северо-Кавказского федерального университета, 2023)
Human capital is both the main factor of economic development and the goal of the society. Education, culture and healthcare form the foundation for the growth and development of human capital, which contributes to the growth of labor productivity, social progress and economic recovery. It is especially significant in the regional dimension from the position of overcoming the imbalances of social and economic development of individual territories of the country. The article analyzes the main components of human capital, assesses the factors determining the possibility of accumulation and development of regional human capital. The results of the research helped identify creative and cultural capital as a part of main elements of human capital and justify the priority of regional programs in ensuring its development.